ICT4Ag: Creating an enabling environment - Ohiomoba, Ifidon (Technical Centre for Agricultural and Rural Cooperation, 2013)
ACP agriculture is yet to benefit fully from the potential of ICTs. New approaches are needed to ensure the systematic use of ICT solutions, and to create an enabling environment in which ICTs could enhance the impact of agricultural development programmes.